Pindaho : Sistem Informasi Jasa Angkut Berbasis Web: Web-based Transportation Services Information System - Hernanda, Rizka; Gunawan, Dedi (AI Society & STMIK Indonesia, 2024)
The moving process requires thorough preparation from the place of origin to the new location, including arranging goods, finding suitable means of transportation, as well as carrying out the process of loading and unloading and rearranging goods in the new place. However, this process is often faced with various obstacles, such as difficulties in finding available transportation services and difficulties for transportation service owners in promoting their services widely. To overcome these challenges, the use of technology in the form of a web-based transportation service system has been proposed. The Movingo system applies a Software Development Cycle (SDLC) approach, mainly using the waterfall method, and will use the PHP programming language and MySQL database supported by the CodeIgniter framework. In this system, there are three types of access rights, namely admin, driver, and customer. Customers can order the transportation services they want, while drivers have the authority to approve orders and check the goods that have been delivered to customers. Payment is made in cash directly on the spot. To ensure the quality of the system being developed, testing is carried out using the black box method and also the System Usability Scale (SUS). Test results showed that the system worked well, with an average score of 79 on the SUS, indicating Good qualifications.